The prosecution and defence of black defendants in drug trials. Evidence of claims-making - Kalunta-Crumpton, Anita (The British journal of criminology, 1998)
Prosecuting and defence barristers' participation in trial is of principal significance in determining a case outcome. It is the intention of this article to examine the role that barristers play in shaping the representation of black people in the criminal statistics. Detailed observations of drug offence trials concerning black defendants demonstrate this role in the way barristers socially construct drug cases through the process of claims-making - an activity that entails an impressive utilization of language to persuade. The study describes how, within this claims-making process, racially imbued knowledge seemed to inform barristers' presentation of the defendants' cases before the jury. In conclusion, the findings question the authenticity of criminal statistics as an indication of guilt